2019
DOI: 10.1007/s12119-019-09635-1
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Sexism and Gay Men in the US and UK

Abstract: Intersectionality addresses power structures and systemic oppressions tied to marginalized identities, which qualitatively differentiates marginalized individuals from each other. This study examines the intersection of gender, sexuality, and nationality to understand possible sexist attitudes of gay men in the US and UK. It uses the Ambivalent Sexism Inventory along with five predictor variables: religiosity, political ideology, nationalism, anti-immigration attitudes, and news consumption. The importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Although men tend to have more power than women in most societies, the precise cultural and historical context in which gender relationships are lived cannot be ignored. Indeed, there is some evidence that predictors and consequences of sexism can vary across societies as culturally similar as the UK and the USA 174 . At the same time, some of the research reviewed here reported similar phenomena across different cultural settings.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Although men tend to have more power than women in most societies, the precise cultural and historical context in which gender relationships are lived cannot be ignored. Indeed, there is some evidence that predictors and consequences of sexism can vary across societies as culturally similar as the UK and the USA 174 . At the same time, some of the research reviewed here reported similar phenomena across different cultural settings.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…AS establishes a masculine heterosexual domination in society that not only discriminates women, but also expresses hostility and discrimination towards non-heterosexual people [ 20 ]. Currently, there is consolidated evidence of the association of sex with AS, with men being more sexist than women [ 21 23 ], but information on the association between sexual orientation and AS is still scarce and heterogeneous [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, the influence of sexism on the rejection of anything that deviates from heteronormativity has been studied on several occasions. However, the connection between having a non-heterosexual orientation and sexist beliefs rarely appears in most of the research done ( Blumell and Rodriguez, 2019 ; Cowie et al, 2019 ). In Spain, no studies on sexism have taken sexual orientation into account as a mediator variable.…”
Section: Introductionmentioning
confidence: 99%
“…It looks at the differences according to sexual orientation and gender identity and the importance of different variables such as resistance to heterosexual norms, political affiliation and contact with LGB individuals. Since this is an exploratory study, which seeks to intersectionally elucidate the construct of sexism among little-studied populations (such as LGB; López-Sáez et al, 2019 ), no hypotheses were made beforehand, following a proposal similar to that by ( Blumell and Rodriguez, 2019 ).…”
Section: Introductionmentioning
confidence: 99%